성격검사 및 전산화신경심리검사를 활용한 사상체질별 성격, 인지 특성 연구 - 김미선; Misun Kim; 안윤영; Yunyoung An; 김락형; Lakhyung Kim (동의신경정신과학회지, 2017)
Objectives: The purpose of this study is to study the personality traits and cognitive characteristics of the Sasang constitution by comparing the Personality Test and Neuropsychological Test. Methods: A total of 121 subjects were analyzed with the results of a Two Step Questionnaire for the Sasang Constitution Diagnosis (TS-QSCD). Among them, the Personality Tests (SPQ, EPQ, TCI) and the Neuropsychological Tests (A-VLT, CPM, Stroop-CWIT, WCST) were processed and analyzed for Soyangin, Taeeumin, Soeumin. Results: 1. In the results of the SPQ, the Soyangin showed a significantly higher score than did the Taeeumin and Soeumin in Behavior, Emotionality, Cognition, as well as the Total Score. The SPQ-C score and SPQ-T were significantly higher for Soyangin, Soeumin and Taeeumin, in that order. 2. In the results of the EPQ, the Soyangin showed a significantly higher score than did the Taeeumin and Soeumin in Extraversion - introversion. Soeumin showed a significantly higher score than did the Soyangin and Taeeumin in Neuroticism. Soyangin also showed a significantly higher score than Taeeumin in Venturesomeness. 3. For the results of the TCI, the Soyangin showed a significantly lower score than did Taeeumin and Soeumin in Harm-Avoidance, but a significantly higher score in Persistence and Self-Directedness. Soyangin and Taeeumin showed a significantly higher score than did Soeumin for the total score of Self-Directedness+Cooperativeness. 4. The results of the Computerized Neuropsychological Tests (A-VLT, CPM, Stroop-CWIT, WCST) showed no significant differences between the Sasang constitution. Conclusions: The EPQ, TCI score showed significant differences between the Sasang constitution. But the Computerized Neuropsychological Tests developed to evaluate cognitive abilities did not show differences between the constitutional individuals and showed limitations as a research tool. Further studies are needed to devise a research method for ascertaining the cognitive behavioral characteristics of the Sasang constitution.